Healthcare personel's performance: The role of job crafting and work engagement - Ranihusna, Desti; Ulfa, Unzilla Ainun; Wulansari, Nury Ariani (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
Organizations and human resources face rapid changes and significant challenges, including employees of Balai Kesehatan Masyarakat Semarang and Ambarawa to require them to adapt and find new effective ways to deal with these changes and challenges. Patient visits and health services data are evaluated and assessed to measure how good the health level service is. This research aims to determine that job crafting and work engagement can improve the performance of employees at Balai Kesehatan Masyarakat Semarang and Ambarawa. The population of this research is all employees of Balai Kesehatan Masyarakat Semarang and Ambarawa, totaling 109 employees, and the sample obtained was 86 people. The data collection method used observation and questionnaires, and the data analysis method used the SEM PLS method with the SmartPLS 3.0 analysis. The results showed that all hypotheses in this research were accepted and showed a positive and significant effect. Suggestions for further research can involve the entire UPT Balai Kesehatan Masyarakat Central Java Province.